Pembentukan Karakter Religius Siswa Melalui Kegiatan Keagamaan di Madrasah - M. Ubaidillah Al Anshory; Muhammad Arif Syihabuddin (Kartika: Jurnal Studi Keislaman, 2026)
The formation of religious character is an important aspect of education to equip students to have good morals amidst the challenges of moral degradation. Education does not only focus on mastering knowledge, but also on internalizing religious values ​​in students' daily lives. This research aims to analyze the formation of students' religious character through religious activities at MTs Hidayatul Ummah and MTs Mambaus Sholihin 5 Balongpanggang. This research uses a qualitative approach with a multisite case study type. Data was collected through observation, interviews and documentation involving school principals, teachers and students. Data analysis was carried out descriptively with stages of data reduction, data presentation, and drawing conclusions, and its validity was tested through triangulation and diligent observation. The results of the research show that the formation of religious character is carried out through teacher example, habituation to religious activities, and instilling discipline. Activities such as congregational prayers, murojaah, and moral training are the main means of internalizing religious values, and are supported by cooperation between schools and parents. The impact can be seen in the formation of honest attitudes, discipline, humility, tolerance and a firm personality in students.